ANALISIS POTENSI AGROWISATA UNTUK PENGEMBANGAN EKONOMI LOKAL DI KAWASAN PANORAMA BARU KOTA BUKITTINGGI - Nana Lili Andriani; Fashbir Noor Sidin; Melinda Noer (Jurnal Planologi, 2020)
Agrotourism is the most beneficial form of tourism for regional development because it can be used as a strategy for local economic development as well as for the preservation of local natural and cultural resources. With the concept of local economic development, in the formulation of its policy to use the maximum potential of the local potential for agrotourism development. Panorama Baru is one of the areas that has long been directed to become an agro-tourism area in the city of Bukittinggi but its development is still very limited so it has not been able to provide economic benefits for the local community. The purpose of this study is to analyze the characteristics and potential that exists as a guide for more operational planning for development actors so that agrotourism can contribute to local economic development. The data analysis method uses descriptive analysis to identify regional characteristics and spatial analysis to see the potential distribution. The results show that Panorama Baru has characteristics suitable for agro-tourism development and until now there are still many potentials that can be developed into agro-tourism attractions. Agro-tourism development is directed at a community-based model but still requires serious support from the government and other stakeholders.